2012
DOI: 10.1371/journal.pone.0050792
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of the German General Population toward Early Diagnosis of Dementia – Results of a Representative Telephone Survey

Abstract: BackgroundEarly detection of dementia has clearly improved. Even though none of the currently available treatments for the most common form of dementia, Alzheimer’s dementia, promises a cure, early diagnosis provides several benefits for patients, caregivers, and health care systems. This study aimed to describe attitudes toward early diagnosis of dementia in the German general population.MethodsA representative telephone survey of the German population aged 18+ years (n = 1,002) was conducted in 2011.ResultsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 34 publications
1
35
1
7
Order By: Relevance
“…Unlike our finding of gender not being associated with acceptance, Luck et al (2012) found, in a German population, men to be more accepting of screening, as did a US study (Holsinger et al, 2011). Again contrary to our findings, a US study of acceptance of screening for four diseases, including AD, found male gender and younger age (as well as lower educational attainment) to be associated with increased acceptance of testing but did not report the AD results separately (Neumann et al, 2012).…”
Section: Comparison With Previous Literaturecontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike our finding of gender not being associated with acceptance, Luck et al (2012) found, in a German population, men to be more accepting of screening, as did a US study (Holsinger et al, 2011). Again contrary to our findings, a US study of acceptance of screening for four diseases, including AD, found male gender and younger age (as well as lower educational attainment) to be associated with increased acceptance of testing but did not report the AD results separately (Neumann et al, 2012).…”
Section: Comparison With Previous Literaturecontrasting
confidence: 99%
“…Our finding of 66.2% of patients reporting they would like to know if they have dementia is similar to that of a German study that found 69% of participants (18 years and older) would be willing to be examined for early diagnosis of dementia (Luck et al ., ). In a telephone survey of US adults, 79% were willing to accept a hypothetical perfectly accurate blood test to predict AD.…”
Section: Discussionmentioning
confidence: 97%
“…Cognitive status was assessed using the German version of the MMSE [22]. In the analyses, we used the total MMSE score and a categorization indicating "no cognitive impairment" (score 27-30), "mild" (score 20-26), "moderate" (score [10][11][12][13][14][15][16][17][18][19], and "severe cognitive impairment" (score 0-9). Depression was operationalized using the score of the Geriatric Depression Scale [23,24] as a dichotomized variable ("no depression," score 0-5; "depression," score 6-15).…”
Section: Procedures and Instrumentsmentioning
confidence: 99%
“…Only 1.5% of the patients reported that they worried more about their health after the screening. Other surveys revealed that a clear majority of participants would prefer to be diagnosed early and expected to be properly informed about their diagnosis [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…Hausärzte und Hausärztinnen sind oft die ersten Ansprechpartner für Menschen mit Gedächtnisbeschwer-den oder Demenz und deren Angehörige [9]. Insofern sind sie es, die mit dem Problem der Fahrtauglichkeit bei Demenz konfrontiert werden und dieses früh ansprechen könnten.…”
Section: Introductionunclassified